Expression of a Degradation‐Resistant β‐Catenin Mutant in Osteocytes Protects the Skeleton From Mechanodeprivation‐Induced Bone Wasting. (5th August 2019) - Bullock, Whitney A; Hoggatt, April M; Horan, Daniel J; Lewis, Karl J; Yokota, Hiroki; Hann, Steven; Warman, Matthew L; Sebastian, Aimy; Loots, Gabriela G; Pavalko, Fredrick M; Robling, Alexander G
ABSTRACT: Mechanical stimulation is a key regulator of bone mass, maintenance, and turnover. Wnt signaling is a key regulator of mechanotransduction in bone, but the role of β‐catenin—an intracellular signaling node in the canonical Wnt pathway—in disuse mechanotransduction is not defined. Using the β‐catenin exon 3 flox (constitutively active [CA]) mouse model, in conjunction with a tamoxifen‐inducible, osteocyte‐selective Cre driver, we evaluated the effects of degradation‐resistant β‐catenin on bone properties during disuse. We hypothesized that if β‐catenin plays an important role in Wnt‐mediated osteoprotection, then artificial stabilization of β‐catenin in osteocytes would protect the limbs from disuse‐induced bone wasting. Two disuse models were tested: tail suspension, which models fluid shift, and botulinum‐toxin (botox)‐induced muscle paralysis, which models loss of muscle force. Tail suspension was associated with a significant loss of tibial bone mass and density, reduced architectural properties, and decreased bone formation indices in uninduced (control) mice, as assessed by dual‐energy X‐ray absorptiometry (DXA), micro‐computed tomography (µCT), and histomorphometry. Activation of the βcatCA allele in tail‐suspended mice resulted in little to no change in those properties; ie, these mice were protected from bone loss. Similar protective effects were observed among botox‐treated mice when the βcatCA was activated. RNAseq analysis of altered gene regulation in tail‐suspended mice yielded 35 genes, including Wnt11, Gli1, Nell1, Gdf5, and Pgf, which were significantly differentially regulated between tail‐suspended β‐catenin stabilized mice and tail‐suspended nonstabilized mice. Our findings indicate that selectively targeting/blocking of β‐catenin degradation in bone cells could have therapeutic implications in mechanically induced bone disease. © 2019 American Society for Bone and Mineral Research.